Adolescent Lifestyle of Gadget Users in Kudus City - Rahmawati, Anik; Soesilowati, Etty; Sanjoto, Tjaturahono Budi (Universitas Negeri Semarang, 2018)
The development of modern technology and information that is accompanied by globalization and modernization has had an impact to the citizen of Kudus lifestye. The changes of Kudus into a cyber-city also affect the lives of adolescents in the Kudus City. It is also affects the use of gadgets in adolescents in the Kudus City because of sufficient parental income levels and demands of the use of technology in educational devices in the Kudus City. This study was conducted in Kudus City because Kudus City is an industrial city which is a religious society and has a program as a cyber City. The purpose of this research is to determine the lifestyle of adolescent users of gadgets in the Kudus City. In addition, this study was also conducted to determine the pattern of family and school education on the lifestyle of adolescents with the development of cyber city in the Kudus City. This type of research is descriptive qualitative research with interactive data analysis. The results of this study is the determination of technology on the adolescent lifestyle of gadget users seen from social interaction, consumption behavior and closely related to the pattern of family and school education in the development of cyber in the Kudus City.